Plant growth promotion via priming with volatile organic compounds emitted from Bacillus vallismortis strain EXTN-1 - Dutta, Swarnalee; Balaraju, Kotnala; Oh, Soh-Young; Lee, Mi-Hyun; Lee, Se Weon; Lee, Yong Hwan; Park, Kyungseok (Frontiers in Microbiology, 2025)
Volatile organic compounds (VOCs) produced by potential plant growth-promoting rhizobacteria (PGPR) play an important role in plant interactions. However, the mechanisms underlying this phenomenon are not well understood. Our findings show that the influence of VOCs from the PGPR strain Bacillus vallismortis (EXTN-1) on tobacco plant growth is dependent on the culture media used. The VOCs released from sugar-rich media such as potato dextrose agar (PDA) and King’s B (KB) media were highly effective. However, exposure to VOCs from nutrient agar (NA), tryptic soy agar (TSA), and Luria-Bertani (LB) resulted in chlorosis and stunted plant growth. This effect was caused by the discharge of a large amount of ammonia that altered the pH of the plant growth media. Seedlings exposed to VOCs for 10 days exhibited improved growth even after the VOCs were eliminated under greenhouse conditions. Priming of seeds with VOCs for 24 and 48 h induced higher growth than the untreated control, and seeds with 48 h exposure were better as compared to 24 h treatment. Chemical characterization of VOCs emitted by EXTN-1 in different media using solid-phase microextraction (SPME) coupled with gas chromatography-mass spectrometry (GC-MS) showed the presence of 2,3-butanedione and monoxime in all spectra. However, 1-butanol was the prominent peak in VOC of EXTN-1 grown in KB and NA, while acetoin was highest in PDA, followed by KB. Heneicosane and benzaldehyde were exclusively produced in NA media, and these synthetic compounds improved growth in the I-plate assay. This work indicates that VOCs released from EXTN-1 are important for the growth-promoting effect of EXTN-1.